2011
DOI: 10.1177/0020764011408651
|View full text |Cite
|
Sign up to set email alerts
|

Employment status, inflation and suicidal behaviour: An analysis of a stratified sample in Italy

Abstract: The reported vulnerability to suicidal behaviours among the PE as inflation rises underlines the need of effective support strategies for both genders in times of economic downturns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 61 publications
0
6
0
1
Order By: Relevance
“…The present study included several control variables (e.g., sociodemographic, behavioural, and psychopathological factors) that have previously been reported to be associated with both religiosity and suicidality. Specifically, sex , age , ethnicity , income , marital status , employment , loneliness , social support , number of stressful life events , perceived stress , chronic physical conditions , smoking status , alcohol dependence , drug use , and common mental disorders were considered as control variables in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The present study included several control variables (e.g., sociodemographic, behavioural, and psychopathological factors) that have previously been reported to be associated with both religiosity and suicidality. Specifically, sex , age , ethnicity , income , marital status , employment , loneliness , social support , number of stressful life events , perceived stress , chronic physical conditions , smoking status , alcohol dependence , drug use , and common mental disorders were considered as control variables in this study.…”
Section: Methodsmentioning
confidence: 99%
“…An Italian study investigating the relationship between inflation, employment status and suicidal behavior in a stratified sample showed that the unemployed were at higher suicide risk than the employed and in particular, this was higher in the unemployed who had been previously employed (Solano et al 2012). The change in social status caused by the job-loss would have determined a further vulnerability to inflation in this sample compared with the unemployed who never worked and those employed (Solano et al 2012). These recent studies show a complex interplay of socio-economic factors influencing suicidal behaviorswhich is still an open question.…”
Section: A New Conceptualization Of Suicide Within Economies Of Powermentioning
confidence: 72%
“…Considering other economic parameters, an increase in gross domestic product per capita and gross value added negative correlated with suicide rates in Europe (Breuer, 2015). An Italian study investigating the relationship between inflation, employment status and suicidal behavior in a stratified sample showed that the unemployed were at higher suicide risk than the employed and in particular, this was higher in the unemployed who had been previously employed (Solano et al 2012). The change in social status caused by the job-loss would have determined a further vulnerability to inflation in this sample compared with the unemployed who never worked and those employed (Solano et al 2012).…”
Section: A New Conceptualization Of Suicide Within Economies Of Powermentioning
confidence: 99%
See 1 more Smart Citation
“…Udruženost stope nezaposlenosti i stope pokušaja samoubistva je vrlo česta [10]. Dejstvu nezaposlenosti verovatno doprinose faktori kao što su ugroženost ekonomske egzistencije, izolovanost, osećanje beznađa.…”
Section: Diskusijaunclassified